Quantum effects in curved spaces: from the particle concept to field theory - Vitenti, Sandro Dias Pinto (Cadernos de Astronomia, 2025)
Quantum field theory is currently the most accurate description of matter, but this framework is the result of a long evolution of the concept of particle in physics.In this article, we trace this development: starting from classical mechanics, where particles are treated as point-like objects; moving to quantum mechanics, where they are described as waves associated with probabilities; and finally arriving at quantum field theory, where particles appear as excitations of fundamental fields. We show that in curved or expanding spacetimes, the definition of a particle is no longer unique: different observers can adopt different vacuum states and consequently identify particles in different ways. We also discuss the role of the quantum vacuum and its connection to the cosmological constant problem,one of the major open questions in contemporary physics. By connecting quantum theory, general relativity, and cosmology, the article addresses both the progress achieved and the conceptual challenges that remain in describing the universe at its most extreme scales.
Keywords: quantum field theory; curved spacetime; quantum vacuum; particle concept; cosmological constant; quantum cosmology; general relativity